Comparisons of Longitudinal Trajectories of Social Competence: Parent Ratings of Children With Cochlear Implants Versus Hearing Peers. Issue 2 (February 2016) - Hoffman, Michael F.; Cejas, Ivette; Quittner, Alexandra L.
Abstract : Objective: To evaluate the longitudinal effects of cochlear implantation (CIs) on young, deaf children's social competence over 5 years of implant use and compare their social skills to those of same-aged, hearing peers. Study Design: Prospective, longitudinal between- and within-subjects design, with assessments completed 3 times over 5 years. Setting: This study was conducted at 6 cochlear implant centers and two preschools that enrolled both CI and hearing children. Patients: Parents of 132 children with CIs and 67 age-matched hearing controls completed the study measures. Children were between 5 and 9 years of age at the first time point. Interventions: Cochlear implantation and speech-language therapy. Main Outcome Measures: Three subscales were drawn from 2 standardized measures of behavioral and social functioning, the Behavioral Assessment Scale for Children (Adaptability, Social Skills) and the Social Skills Rating System (Social Skills). A latent social competence variable was created using multiple subscales, which was modeled over time. Results: Parent data indicated that children with CIs were delayed in comparison to their hearing peers on the social competence latent variable across all time points. Further, there was minimal evidence of "catch-up" growth over this 5-year period. Conclusion: Children with CIs continued to experience delays in social competence after several years of implant use. Despite documented gains in oral language, deficits in social competence remained. To date, no interventions for children with CIs have targeted these social and behavioral skills. Thus, interventions that address the functioning of the "whole child" following cochlear implantation are needed.